1996
DOI: 10.1080/03079459608419141
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology and immunohistochemistry of renal lesions due to infectious bronchitis virus in chicks

Abstract: SUMMARYTwo-day-old specific-pathogen-free chicks were inoculated intranasally with the MA-87 strain of infectious bronchitis virus, and trachea and kidney lesions studied histologically and immunohistochemically. Lesions and viral antigen were first detected in the trachea; severe damage was then observed in the kidney. Viral antigen appeared prior to the development of renal lesions and was detected in the cytoplasm of epithelial cells by 4 days post-inoculation (p.i.). The epithelial cells of the collecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 12 publications
6
56
1
3
Order By: Relevance
“…However, unlike previous studies where either severe kidney damage (Butcher et al, 1990;Chen et al, 1996) or alterations to the reproductive tract (Crinion & Hofstad, 1971) was reported following M41 infection, in our study no remarkable lesions or presence of viral RNA was detected in the other organs. This discrepancy might be caused by different passage levels, experimental conditions and design, breed or age of the birds, or by the use of different strains of M41.…”
Section: Discussioncontrasting
confidence: 54%
“…However, unlike previous studies where either severe kidney damage (Butcher et al, 1990;Chen et al, 1996) or alterations to the reproductive tract (Crinion & Hofstad, 1971) was reported following M41 infection, in our study no remarkable lesions or presence of viral RNA was detected in the other organs. This discrepancy might be caused by different passage levels, experimental conditions and design, breed or age of the birds, or by the use of different strains of M41.…”
Section: Discussioncontrasting
confidence: 54%
“…The performance of the IPA in detecting IBV antigen after inoculation of SPF chickens compares very favourably with IFA (Nakamura et al, 1991;Owen et al, 1991;Janse et al, 1994;Chen et al, 1996). Naqi (1990) showed that IBV could be detected by IPA in the CAM of inoculated eggs within 15 h p.i., with a detection limit of 10 6.2 EID 50 .…”
Section: Detection Of Ibv Antigenmentioning
confidence: 86%
“…Briefly, the rehydrated sections were placed in plastic containers filled with 0.01 M phosphate buffer (PB), pH 6.0 and autoclaved at 121°C 3 under 2 atm for 15 min. After autoclaving, the containers were allowed to cool prior to incubation overnight at 4°C with the primary antibody, either rabbit anti-S6 strain of MG serum (1:10,000, hyperimmune serum prepared in our laboratory), rabbit anti-chicken IgA serum (1:1,000, affinity purified, Bethyl Lab Inc., Montgomery), mouse monoclonal antibody recognizing the nucleoprotein of IBV (Chen et al, 1996), chicken IgG or IgM (1:10,000, prepared by Hoshi). They were then reacted with either peroxidaselabeled goat anti-rabbit IgG, peroxidase-labeled rabbit anti-mouse IgG (Sigma Chemical Co., St Louis), a Histofine SAB-PO kit for rabbit primary antibody or mouse primary antibody (Nichirei Inc., Japan), visualized with 3-amino-9-ethylcarbazole (Sigma Chemical Co., St Louis) -hydrogen peroxide staining solution, and counterstained lightly with Mayer's haematoxylin (McManus & Mowry, 1964).…”
mentioning
confidence: 99%